(untitled) - Lukoff, Kyle (New York, New York, 2025)
After coming out as trans, fourteen-year-old A is forced to attend weekly Save Our Sons and Daughters meetings, where he uncovers the terrifying truth that the group is run by a demon feeding on their pain and is part of a larger, darker force preying on the worlds vulnerable.
Ages 14 and up.
Keywords: Jewish people; Fiction; Supernatural; Fiction; Friendship; Fiction; Demons; Fiction; Conversion therapy; Fiction; Fiction; Transgender people; Juvenile fiction; Supernatural; Juvenile fiction; Friendship; Juvenile fiction; Demonology; Juvenile fiction; Conversion therapy; Juvenile fiction; Jewish transgender people; Novels